Three essays on housing markets: Price dispersion, dynamic location choices and family investments - Christian Langholz Carstensen (University of Copenhagen, Department of Economics, 2020)
This thesis consists of three independent chapters which all revolve around the investment decisions of households on the housing market. Although the chapters vary in method and subject, they all emphasize the distributional consequences of a policy or business cycle uctuation.
Keywords: 330